PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR MANUFAKTUR DI BURSA EFEK INDONESIA - Nanik Lestari; Donny Rizki Septian (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2018)
Abstract: The purpose of this reasearch is to give empirical evidence about the relationship between working capital management to profitability for companies and investors. This research uses purposive sampling method as sampling method. The population of this research is manufacture companies that are listed on Indonesian Stock Market from 2010 to 2014 with 230 sample in total. This research uses panel data regression significant with eviews 7.0 program. This research have independent variables which are working capital factors with variable measurements as follows: days on receivables, days on payables, days on inventories, and cash conversion cycle. Dependent variable in this research is profitability with return on assets as variable measurement and control variables in this research are firm size, sales growth, leverage, current asset ratio, and current liability ratio. This research shows that days on account receivables and cash conversion cycle are affecting return on assets variable and days on payables and day on inventory variable are not affecting return on assets variable. Keywords: Working Capital, Panel Data Regression, Profitability